If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 1 = y Reorder the terms: 1 + -5x = y Solving 1 + -5x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5x = -1 + y Combine like terms: 1 + -1 = 0 0 + -5x = -1 + y -5x = -1 + y Divide each side by '-5'. x = 0.2 + -0.2y Simplifying x = 0.2 + -0.2y
| .2x+.3(x+1)=2 | | 6x^2-2=-50 | | y[n]+0.4y[n-1]=3x[n] | | (X-11)(7x+1)=0 | | 3+30x=15x+30 | | 6x+3y=9fory | | 1/5x-3=-6 | | Ln(3x-2)=10 | | 14A+13B-6A+7= | | 10=12-8 | | 4+4=-6 | | y=3-1/2x | | 5(a-1)-4(a-2)=2(5a+20) | | 10=2x-86 | | F(9)=3 | | 1000=r^3/2 | | 3(X+2X)+9R= | | 20y+3x=50 | | ((3y+4)*2)+((y+3)*2)=70 | | .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x |